Political Security in Southern Africa: Historical, Contemporary and Futuristic Perspectives (The Strategic Review for Southern Africa, 2020)
Political security has been widely argued to be one of the fundamental pillars of development, stability and prosperity, as it in turn lays the ground and conducive environment for the attainment of other forms of human security, namely economic security, food security, health security, environmental security, personal security and community security. Political security, as stated by the United Nations Human Development Report (994), entails defense against the different forms of political oppression, respect to human rights, and protection from threats of militarization. Therefore, the purpose of this paper was to establish the extent towhich the concept of Political Security is applicable in Southern Africa within the context of a fast-globalizing landscape through analyzing historical and contemporary trends as well as forecasting future trends and patterns of political security in Southern Africa. Methodologically, the paper used secondary data sources to examine historical and contemporary trends in political security within Southern African countries whilst the International Futures (IFs) model, a comprehensive integrated modeling system, was used as a forecasting tool to establish the likelihood of political security within the different Southern African countries and future political security dynamics and complexities within Southern African countries whilst at the same timeproviding an outlook of the situation within the next 12 years. The study results show varying levels of political security in the region, with the majority of the Southern African states showing worsening political security situation by 2030, except Mauritius, Botswana, Namibia, Seychelles, and South Africa. Recommendations are suggested in the form of national and regional policy and strategic interventions that are key in strengthening political security within Southern Africa.